RNA-dependent chromatin association of transcription elongation factors and Pol II CTD kinases - Sofia Battaglia; Michael Lidschreiber; Carlo Baejen; Phillipp Torkler; Seychelle M Vos; Patrick Cramer (eLife, 2017)
For transcription through chromatin, RNA polymerase (Pol) II associates with elongation factors (EFs). Here we show that many EFs crosslink to RNA emerging from transcribing Pol II in the yeast Saccharomyces cerevisiae. Most EFs crosslink preferentially to mRNAs, rather than unstable non-coding RNAs. RNA contributes to chromatin association of many EFs, including the Pol II serine 2 kinases Ctk1 and Bur1 and the histone H3 methyltransferases Set1 and Set2. The Ctk1 kinase complex binds RNA in vitro, consistent with direct EF-RNA interaction. Set1 recruitment to genes in vivo depends on its RNA recognition motifs (RRMs). These results strongly suggest that nascent RNA contributes to EF recruitment to transcribing Pol II. We propose that EF-RNA interactions facilitate assembly of the elongation complex on transcribed genes when RNA emerges from Pol II, and that loss of EF-RNA interactions upon RNA cleavage at the polyadenylation site triggers disassembly of the elongation complex.